Pro and Con of the Recitation Tradition at Cemeteries In the Bireuen Community (A Study of Living Hadith) - Zikraa, Zikraa; Nurliana Damanik (al-Afkar, Journal For Islamic Studies, 2025)
This tradition aims to pray for the deceased and is believed to provide benefits for those who have died. However, this practice has caused debate among scholars and the community. The pro group argues that this tradition is included in charity and beneficial knowledge, while the contra group considers it a bid'ah that has no basis in the sunnah of the Prophet Muhammad SAW. This study aims to analyze the tradition of reciting the Koran at funerals from the perspective of hadith and to see the social and cultural implications of this practice. This study uses a qualitative approach with hadith analysis and religious ethnography methods. Data were collected through literature studies, in-depth interviews with religious and community leaders, participant observation, and analysis of Islamic documents and fatwas. The results of the study show that there is no explicit evidence in the hadith that directly justifies or prohibits this tradition. Differences of opinion regarding this practice are more based on differences in methodology in understanding the hadith and the principles of bid'ah in Islam. In addition, this study found that the tradition of reciting the Koran at funerals has a significant social function in strengthening community solidarity and maintaining social harmony. The attitude of tolerance applied by the Bireuen community in responding to differences of opinion shows that diversity in religious understanding does not always cause conflict, but can be managed through an inclusive approach. The implications of this study indicate the need for broader education regarding the understanding of hadith and bid'ah so that the community can assess religious practices more objectively. This study contributes to the study of Islam and culture by highlighting how local traditions can adapt to Islamic teachings in a dynamic social context.